Urgensi Pembentukan Wilayah Pertambangan Rakyat Dalam Formulasi Kebijakan Pertambangan Timah Di Bangka Belitung - Firsantara, Armitran; Hikmah, Faidatul (Fakultas Hukum Universitas Bangka Belitung, 2024)
This study aims to elaborate on the urgency of establishing People's Mining Areas (WPR) in the governance of tin mining in Bangka Belitung post the centralization of mining authority. Utilizing a juridical-normative research method and a statutory approach, this study examines the reality of das sein with the relevance of das sollen to find legal gaps and replicate strategic solutions. The analysis results in this study indicate that the issuance of Law No. 3 of 2020 and Presidential Regulation No. 55 of 2022 has explicitly separated the central and regional government authorities. One of the regional authorities is in the field of People's Mining License (IPR). Although the IPR mechanism has been regulated since Law No. 4 of 2009, its implementation is still imbalanced and not efficient in Bangka Belitung. From 2009-2020, the number of illegal tin miners continued to increase, while the number of IPRs utilized remained very limited. This condition has not changed significantly from the period 1998-2009 when illegal tin mining began to encroach. Therefore, by delegating the IPR back to the regions, the government needs to prepare mechanisms to optimize mining governance, including through the establishment of WPRs which become the basic condition for granting IPRs.